2020
DOI: 10.1002/anie.202009449
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenes as Key Components for Low‐Dimensional (Photo)electrocatalytic Nanohybrid Materials

Abstract: Recent advances in the area of quantum dots (QDs) have shown their wide range of applications that extend from sensing [50] and bioimaging to catalytic water splitting owing to their remarkable electronic,e lectrochemical, optical, and catalytic properties. [51, 52] Thes ynthesis of QDs can be Alain R. Puente Santiago received his PhD degree in Physical Chemistry with distinction from the University of Cordova, Spain in 2017. He is currently apostdoctoral fellow in Prof. Luis Echegoyen's group in the Chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 189 publications
2
46
0
Order By: Relevance
“…Low-dimensional catalytic materials have recently impacted the scientific community as promising functional building blocks to construct highly efficient supramolecular nanoscale structures for water electrocatalysis. , A wide portfolio of heterostructures can be obtained from the noncovalent integration of 0D, 1D, and 2D nanomaterials into 0D–1D, 0D–2D, 1D–2D, and 2D–2D hybrids to achieve sustainable alternatives for advanced electrocatalytic systems . The electronic structures and catalytic performances of supramolecular nanoassemblies have been starting to be tailored by controlling the interfacial interactions between their components, thus paving the way toward a new generation of tunable molecular electrocatalysts. , Among them, the noncovalent heterostructures based on metal-free carbon nanomaterials are gaining special interest due to their unique physicochemical properties such as large surface areas, excellent electronic and mechanical properties, and their affordable prices, which allow them to compete with the traditional noble-metal-based electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dimensional catalytic materials have recently impacted the scientific community as promising functional building blocks to construct highly efficient supramolecular nanoscale structures for water electrocatalysis. , A wide portfolio of heterostructures can be obtained from the noncovalent integration of 0D, 1D, and 2D nanomaterials into 0D–1D, 0D–2D, 1D–2D, and 2D–2D hybrids to achieve sustainable alternatives for advanced electrocatalytic systems . The electronic structures and catalytic performances of supramolecular nanoassemblies have been starting to be tailored by controlling the interfacial interactions between their components, thus paving the way toward a new generation of tunable molecular electrocatalysts. , Among them, the noncovalent heterostructures based on metal-free carbon nanomaterials are gaining special interest due to their unique physicochemical properties such as large surface areas, excellent electronic and mechanical properties, and their affordable prices, which allow them to compete with the traditional noble-metal-based electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interface engineering of 2D nanostructures with other LD architectures could expand their potential to develop new nano-electrocatalytic systems. In this sense, the short-range interfacial interactions of two LD materials can promote plenty of high-speed electron pathways and a simultaneous electronic coupling, thus speeding up the ET processes at the interface as well as optimizing the energy adsorption states of the intermediate catalytic species. , Buckminsterfullerene (C 60 ) is a 0D carbon structure that exhibits extraordinary electron-accepting properties and high affinity to construct supramolecular assemblies, thus becoming strong candidates to build efficient multifunctional metal-free hybrid electrocatalysts. , The integration of C 60 molecules into the BCN network could generate new tunable interfacial active sites as a consequence of the electronic flow between both LD materials, thus boosting the electrocatalytic properties of the assembled materials compared with their individual components.…”
Section: Introductionmentioning
confidence: 99%
“…In the preparation of nanotubes from a carbon source, the composition, size, geometry, and symmetry of the TM clusters, acting as SWNT growing seeds, play a crucial role on their interactions with carbon-based molecules such as CO. For these reasons, cluster–CO interactions are attractive but also these types of adsorption allow us to synthesize different C x nanomaterials such as nanowires, nanodots, or even fullerenes. ,,, More recently, the interactions between small iron clusters with one and two CO molecules were addressed . It was found that Fe n effectively activate the CO bond .…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been attempted to maximize the intrinsic HER catalytic activity of LD carbon-based nanomaterials. The overall electrocatalytic yields are mainly controlled by the adsorption energy of the reaction intermediates and the electronic properties of the catalyst surfaces . Therefore, the introduction of single metal atoms into the sp 2 carbon framework has been explored to engineer the electronic structure and increase the catalytic performance of the materials .…”
mentioning
confidence: 99%